2012
DOI: 10.1002/acr.21655
|View full text |Cite
|
Sign up to set email alerts
|

Association of slower walking speed with incident knee osteoarthritis–related outcomes

Abstract: Objective To determine whether slower walking speed was associated with increased risk of incident hip and knee osteoarthritis (OA)-related outcomes. Methods After providing informed consent, community-dwelling participants in the Johnston County Osteoarthritis Project completed two home-based interviews and an additional clinic visit for radiographic and physical evaluation. One thousand eight hundred fifty eight non-institutionalized residents age 45 years or older living for at least one year in one of si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
43
1
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 46 publications
3
43
1
3
Order By: Relevance
“…These results indicate that the benefit of having daughter(s) for the elderly parents may be more evident with respect to mental health, which is closely related to emotional care, rather than physical health and subjective well-being, which often demands good financial support. It has been shown that financial support could help to provide necessary facilities and a favorable living environment so that ADL disability and poor self-rated health of elders could be avoided even in the presence of a decline in physical health (Feng, Hoenig, Gu, Zeng, & Purser, 2010; Feng, Son, & Zeng, 2015; Purser et al, 2012). It is thus understandable that having daughter(s) did not result in significant benefits for older parents in their ADL capacity, subjective well-being, or deficit index, because, as compared with son(s), Chinese daughter(s) are not as advantageous in providing financial support to their elderly parents.…”
Section: Resultsmentioning
confidence: 99%
“…These results indicate that the benefit of having daughter(s) for the elderly parents may be more evident with respect to mental health, which is closely related to emotional care, rather than physical health and subjective well-being, which often demands good financial support. It has been shown that financial support could help to provide necessary facilities and a favorable living environment so that ADL disability and poor self-rated health of elders could be avoided even in the presence of a decline in physical health (Feng, Hoenig, Gu, Zeng, & Purser, 2010; Feng, Son, & Zeng, 2015; Purser et al, 2012). It is thus understandable that having daughter(s) did not result in significant benefits for older parents in their ADL capacity, subjective well-being, or deficit index, because, as compared with son(s), Chinese daughter(s) are not as advantageous in providing financial support to their elderly parents.…”
Section: Resultsmentioning
confidence: 99%
“…12 However, change in walking speed may provide a more sensitive measure of future osteoarthritis risk than an assessment of gait pace at a single time point. To date no prospective studies have examined longitudinal changes in walking speed and risk of rKOA.…”
Section: Introductionmentioning
confidence: 99%
“…Our group has previously reported significant associations between slower gait speed and finger joint symptoms, after adjustment for hip and knee symptoms and rOA [3]. The vast majority of studies using gait speed in OA focus on knee OA, with fewer looking at hip involvement [34]. One study assessing knee and ankle rOA and symptoms at these two sites found that knee rOA was independently associated with reduced gait speed [48].…”
Section: Discussionmentioning
confidence: 99%
“…Three individuals with implausible values were excluded from the analysis resulting in n=1300 for this outcome. Gait speed has been assessed as a performance-based marker of functional limitation in geriatric conditions including OA [3, 5, 33, 34], and the 8-foot walk test is a reliable measure in older adults (intra-observer ICC >0.7, inter-observer ICC>0.5 [35, 36]).…”
Section: Participants and Methodsmentioning
confidence: 99%